Przemoc rówieśnicza w szkole jako zagrożenie dla dobrostanu uczniów - Borowiak, Magdalena (Studia Edukacyjne, 2026)
The article addresses peer violence in the school environment, focusing on its impact on students’ psychological, emotional, and social well-being. It presents the conceptual framework and typologies of violence, as well as its psychological and social determinants. Attention is drawn to the fact that experiencing violence can significantly disrupt a young person’s sense of safety, emotional balance, and overall sense of happiness. The article highlights the consequences of peer violence, emphasizing its long-term impact on personal development and functioning in social relationships. It moreover stresses the need to foster a school climate based on trust, empathy, and mutual respect. The aim of the article is to highlight the role of a comprehensive, systemic approach to addressing peer violence as a key element in supporting the mental health, well-being, and harmonious development of young people.